DON JUAN MANUEL. RETRATO DE UN PRÍNCIPE - Belda Navarro, Cristobal; Hernández Albadalejo, Elías (Imafronte, 1991)
This paper discusses a series of items related to the altarpieces painted in Genoa by the Italian artist Bernabé de Módena, and now held in the Museum of the Cathedral of Murcia. The activity of the Italian painter and his relation with the family of Prince Don Juan Manuel were already known, but certain aspects of his work for Murcia remained to be elucidated: among those, the possibility of determining the nature and signification of the figures of the donors placed in the lowest reredos. The analysis of them and the hypothesis of considering them as allegorical representations (in which it rules such values as the pride of a lineage and the lofty nature of the patron -accompanied by his daughter, the Queen of Castile Doña Juana Manuel-) serve as a frame to value the principies and ideas of representation of individuals, in the context of their age.